Expanding the Target Market of Mebel Summer Jati Using an Online Catalogue Shared on Facebook - Kelvin Verentino (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Mebel Sumber Jati is an organization that sells furniture items like teak closet, teak table, teak wood seats, spring bed, aluminum glass cabinet, sofa, and eating table. The issue is the deals of this organization continues to decrease since the pandemic occurred. That is the reason behind why this organization actually struggles to get new clients. Nonetheless, the organization intends to grow its objective market, particularly during this pandemic. The arrangement is by extending the objective business sectors through Facebook with an online inventory. On Facebook, the organization will combine the photograph items and the cost just as on the online list. The online catalogue will be distributed on the Facebook marketplace page as a connection. The catalog was made using the theory of Bethina Oksen Bendroff, 2021 Therefore, by having a Facebook with an online list, Mebel Sumber Jati will actually be able to extend their new objective market. Keywords: Facebook, Online catalogue, Expanding target market